B22 Does a peripheral immune response influence muscle pathology in Huntington's disease?. (29th August 2012) - Magnusson-Lind, A; Davidsson, M; Silajdžić, E; Hansen, C; Tabrizi, SJ; Björkqvist, M
Abstract : Background: Classical symptoms of Huntington's Disease (HD) include progressive motor disturbances, cognitive decline and psychiatric problems. In addition to these, HD is further complicated by peripheral pathology, including weight loss and skeletal-muscle wasting. Changes in gene expression in brain, blood and peripheral tissues, such as skeletal muscle, have been shown in human HD as well as in the R6/2 mouse model. Possibly, gene expression alterations in skeletal muscle could offer valuable insight into HD pathology, as well as offer a source of potential disease markers. We have previously shown an early immune activation in HD. Primary monocytes are abnormally activated in response to LPS stimulation and there are increased levels of circulating proinflammatory cytokines early on in the disease. Interestingly, among these are TNF-α and IL-6, which are cytokines that are also known to affect muscle atrophy. Aim: In this study we wanted to investigate the possible relationship between peripheral cytokines and muscle atrophy in HD. Methods: We investigated gene expression of muscle protein genes and selected genes previously shown to be activated by cytokines and linked to muscle atrophy, in skeletal muscle from R6/2 mice and WT littermates by RT-qPCR. Results and conclusions: Here, we describe R6/2 skeletal muscle gene expression changes linked to muscle atrophy and an increase in peripheral cytokines. We find increased expression of caspases as well as decreased expression of muscle proteins, myosin and troponin. Conclusions: Our preliminary results show a plausible link between these gene expression changes and increased levels of cytokines. Funding: This study is supported by EHDN (European Huntington's Disease Network).